Rapamycin prevents acute dendritic injury following seizures. Issue 3 (19th January 2016) - Guo, Dongjun; Zeng, Linghui; Zou, Jia; Chen, Linglin; Rensing, Nicholas; Wong, Michael
Abstract: Objective: Seizures cause acute structural changes in dendrites, which may contribute to cognitive deficits that occur in epilepsy patients. Disruption of the actin cytoskeleton of dendrites likely mediates the structural changes following seizures, but the upstream signaling mechanisms activated by synchronized physiological activity to cause seizure‐induced dendritic injury are not known. In this study, we test the hypothesis that the mechanistic target of rapamycin complex 1 (mTORC1) pathway triggers structural changes in dendrites in response to seizures. Methods: In vivo multiphoton imaging was performed in transgenic mice expressing green fluorescent protein in cortical neurons. The effect of rapamycin pre‐ and posttreatment was tested on kainate‐induced dendritic injury and cofilin‐mediated actin depolymerization. Results: Kainate‐induced seizures caused acute activation of mTORC1 activity, which was prevented by the mTORC1 inhibitor, rapamycin. Rapamycin pretreatment, and to a lesser degree, posttreatment attenuated acute seizure‐induced dendritic injury and correspondingly decreased LIM kinase and cofilin‐mediated depolymerization of actin. Interpretation: The mTORC1 pathway mediates seizure‐induced dendritic injury via depolymerization of actin. These findings have important mechanistic and translational applications for management of seizure‐induced brain injury.